DISCOVERING THE KRAYAN HIGHLAND GEODIVERSITY AND GEOTOURISM POTENTIAL INDONESIA - Ayu Krishna Yuliawati; Shandra Rama Panji Wulung; Mega Fatima Rosana; Mohamad Sapari Dwi Hadian (International Journal of Geotourism Science and Development, 2021)
The Krayan Highland located in the west of Nunukan Regency, North Kalimantan Province, with a history of the earth dating since the Paleozoic era 570-251 million years ago. The area has a beautiful landscape of mountains and hills, home to the local indigenous people called the Dayak Lundayeh Tribe. Krayan Highland is rich in geodiversity, biodiversity and culture diversity. The area has been least developed in terms of infrastructure compared to other areas in the country. The research aims to find and map the geodiversity and geotourism potential of the Krayan Highland. The research method is qualitative method, which data collection is conducted through desk study and field survey. Descriptive, map analysis and content analysis is conducted during this research. The research discovers rich geodiversity in the area, one of them in the Kubah Garam (salt Dome). The Dayak people utilize the salt in the mountain and develop it into a geoproduct with their local indigeneous knowledge. The Krayan Highland has the potentital to be further developed into an aspiring geopark in the future.